2020
DOI: 10.5334/jbsr.2052
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Liver Metastases During Catheter-Directed Liver Interventions: A Comparison between Dual Phase Cone-Beam Computed Tomography and Conventional Contrast-Enhanced Computed Tomography

Abstract: Objectives: To compare the diagnostic performance of intra-arterial dual phase cone-beam computed tomography (DP-CBCT) with contrast-enhanced computed tomography (CE-CT) when characterizing tumor burden in patients with metastatic liver cancer. Materials and Methods: This retrospective study included 29 patients with colorectal (n =10), breast (n = 9) and neuroendocrine (n = 10) liver metastases, referred for catheter-directed treatment. Tumor type, number, maximum size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In this context, other strategies for planning and evaluation before TARE, such as 166 Ho (holmium)-based microspheres, may provide novel insights (Smits et al 2019 ). Further, initial reports have shown that including cone-beam CT (CBCT) to TARE evaluation and treatment work flow may provide additional information about hepatic tumor burden, tumor and tissue perfusion and extrahepatic enhancement compared to digital subtraction angiography (DSA) or 99m Tc-MAA based SPECT/CT imaging (Gormez et al 2020 ; Louie et al 2009 ; Maleux et al 2020 ). However, superiority of CBCT regarding patient safety or treatment evaluation and response has not yet been shown in larger patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, other strategies for planning and evaluation before TARE, such as 166 Ho (holmium)-based microspheres, may provide novel insights (Smits et al 2019 ). Further, initial reports have shown that including cone-beam CT (CBCT) to TARE evaluation and treatment work flow may provide additional information about hepatic tumor burden, tumor and tissue perfusion and extrahepatic enhancement compared to digital subtraction angiography (DSA) or 99m Tc-MAA based SPECT/CT imaging (Gormez et al 2020 ; Louie et al 2009 ; Maleux et al 2020 ). However, superiority of CBCT regarding patient safety or treatment evaluation and response has not yet been shown in larger patient cohorts.…”
Section: Discussionmentioning
confidence: 99%